Development and performance evaluation of alternative road construction material using clay and recycled concrete debris - Noureddine Ouslimane; Jaouad Bensalah; Hanane Barebita; Mohamed Ebntouhami; Youssouf Ali Younous; Mohammad K. Okla; Samir Ibenmoussa; Fouad Dimane; Mustapha Belfaquir (Scientific Reports)
Abstract The use of clay soils in road construction showed various limitations including swelling potential, which adversely affect the stability and durability of road structures. It is thus fitting that this study intended to use a mixture of clay and recycled concrete debris as a sustainable alternative for road construction. Various characterization tests were carried out, including Proctor compaction tests, CBR bearing capacity and odometer tests, as well as X-ray diffraction and infrared spectroscopy analyses to study the mineralogical composition of the samples. The results showed that the addition of 25% of recycled concrete debris improves the density, compaction capacity and strength of the treated soils. The CBR bearing capacity increased from 4.5 to 40% after saturation, while odometer tests revealed potent stability and low deformation under load. The incorporation of concrete debris also reduced swelling indices, resulting in better soil performance. This study demonstrates the effectiveness of recycling concrete debris to reinforce soils used in road construction, offering a sustainable and environmentally friendly solution for road construction.